Efecto del aceite esencial de Citrus aurantium L. en la regeneración muscular en ratones mdx - de Souza, Paula Aiello Tomé [UNESP]; Marques, Maria Júlia; Hiruma-Lima, Clélia Akiko [UNESP]; Matheus, Selma Maria Michelin (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2011)
Duchenne muscular dystrophy (DMD) is a severe X-linked recessive disorder characterized by the progressive loss of muscular strength. Mdx mutant mice show a marked deficiency in dystrophin, which was related to muscle membrane stability. The aim of this study was to verify the possible protective anti-inflammatory effect of citrus oil on mdx muscle fibers. Thus, adult male and female mdx mice (014/06-CEEA) were divided into control and citrus-treated. After 60 days of treatment, one ml of blood was collected for creatine kinase (CK) test. Diaphragm, sternomastoideus, anterior tibial and gastrocnemius muscles were removed and processed according to histological routine methods. The observed alterations indicate a direct effect of citrus. Recent studies have improved the diagnosis of muscular diseases but with no definitions of efficient treatments. Intervention with several therapies is important to many patients presenting muscular dystrophy, which enables them to live longer and be more active, while there is no development of gene therapies.
Effect of Citrus aurantium L. essential oil on muscle regeneration in mdx mice
Keywords: Central nuclei; Citrus aurantium L.; Creatine kinase; Duchenne muscular dystrophy; Mdx mouse; Muscle fiber; Muscle regeneration